PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DANA DESA PADA DESA BOJONGGEDE KECAMATAN BOJONG GEDE KABUPATEN BOGOR - Khairu Syifa Ahyani; Asep Hidayat; Fitri Pebriani Wahyu (Jurnal Inovasi Penelitian, 2022)
Currently it is no longer a public secret that the community is involved and their participation is indeed needed in building the lowest government, namely the village, one of which is through the management of village funds. It was detected that community participation in Bojonggede Village, Bogor Regency has indeed been going well. However, at the time of determining the activities through deliberation, the village authorities had determined earlier, and the community only had to choose. This study uses a descriptive qualitative approach. The data obtained through the process of collecting documentation, observation, and interviews. Analysis of the data using a flow chart which consists of data reduction, data display, and conclusion or verification. It can be concluded that community participation in the management of village funds in Bojonggede Village has been well implemented, although not all residents participated, but the enthusiasm given by the community for each activity organized by the village received a positive response. This can be seen through several dimensions related to community participation, namely participation in decision making, participation in implementing activities, participation in monitoring and evaluation, and participation in the utilization of the results which are to support the management of village funds in Bojonggede Village, Bojong Gede District, Bogor Regency.